Admixture may be extensive among hyperdominant Amazon rainforest tree species - Dick, Christopher W.; Vicentini, Alberto; Vargas, Oscar M.; Larson, Drew A. (New Phytologist, 2021)
Admixture is a mechanism by which species of long-lived plants may acquire novel alleles. However, the potential role of admixture in the origin and maintenance of tropical plant diversity is unclear. We ask whether admixture occurs in an ecologically important clade of Eschweilera (Parvifolia clade, Lecythidaceae), which includes some of the most widespread and abundant tree species in Amazonian forests. Using target capture sequencing, we conducted a detailed phylogenomic investigation of 33 species in the Parvifolia clade and investigated specific hypotheses of admixture within a robust phylogenetic framework. We found strong evidence of admixture among three ecologically dominant species, E. coriacea, E. wachenheimii and E. parviflora, but a lack of evidence for admixture among other lineages. Accepted species were largely distinguishable from one another, as was geographic structure within species. We show that hybridization may play a role in the evolution of the most widespread and ecologically variable Amazonian tree species. While admixture occurs among some species of Eschweilera, it has not led to widespread erosion of most species’ genetic or morphological identities. Therefore, current morphological based species circumscriptions appear to provide a useful characterization of the clade's lineage diversity. © 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation
Keywords: Hybridization; Hyperdominance